LITERATURE REVIEW THE EFFECT OF MUTATION AND LEAVE ON MOTIVATION AND ITS IMPACT ON JOB SATISFACTION - Eric Setiawan (Dinasti International Journal of Education Management And Social Science, 2022)
Mutation and leave is an important thing for employees, especially for employees with agencies or companies that have a distribution of offices throughout Indonesia, the archipelago with geographical conditions of the archipelago and inadequate transportation network conditions, facilities, facilities and infrastructure of each region that is not good and evenly distributed. The pattern of employee placement that spread throughout Indonesia causes many employees to work far from homebase, so it is very important to conduct research on the influence of mutations and leave on motivation and its impact on job satisfaction. Previous relevant research is very important in a scientific article to solidify existing theories and phenomena of influence on variables. The overview given in this article is about the influence of mutations and leave on motivation and its impact on job satisfaction, a literature review of the management of human resources. The preparation of the article aims to compile a hypothesis about the influence of variables that will be used in the research. The research hasil from the library is: 1) mutations affect motivation; 2) Holidays affect motivation; 3) mutations affect job satisfaction; 4) Holidays affect job satisfaction; and 5) Motivation affects job satisfaction.